Ankyrin-B is lipid-modified by S-palmitoylation to promote dendritic membrane scaffolding of voltage-gated sodium channel NaV1.2 in neurons - Gupta, Julie P.; Jenkins, Paul M. (Frontiers in Physiology, 2023)
Neuronal ankyrin-B is an intracellular scaffolding protein that plays multiple roles in the axon. By contrast, relatively little is known about the function of ankyrin-B in dendrites, where ankyrin-B is also localized in mature neurons. Recently, we showed that ankyrin-B acts as a scaffold for the voltage-gated sodium channel, NaV1.2, in dendrites of neocortical pyramidal neurons. How ankyrin-B is itself targeted to the dendritic membrane is not well understood. Here, we report that ankyrin-B is lipid-modified by S-palmitoylation to promote dendritic localization of NaV1.2. We identify the palmitoyl acyl transferase zDHHC17 as a key mediator of ankyrin-B palmitoylation in heterologous cells and in neurons. Additionally, we find that zDHHC17 regulates ankyrin-B protein levels independently of its S-acylation function through a conserved binding mechanism between the ANK repeat domain of zDHHC17 and the zDHHC ankyrin-repeat binding motif of ankyrin-B. We subsequently identify five cysteines in the N-terminal ankyrin repeat domain of ankyrin-B that are necessary for ankyrin-B palmitoylation. Mutation of these five cysteines to alanines not only abolishes ankyrin-B palmitoylation, but also prevents ankyrin-B from scaffolding NaV1.2 at dendritic membranes of neurons due to ankyrin-B’s inability to localize properly at dendrites. Thus, we show palmitoylation is critical for localization and function of ankyrin-B at dendrites. Strikingly, loss of ankyrin-B palmitoylation does not affect ankyrin-B-mediated axonal cargo transport of synaptic vesicle synaptotagmin-1 in neurons. This is the first demonstration of S-palmitoylation of ankyrin-B as an underlying mechanism required for ankyrin-B localization and function in scaffolding Nav1.2 at dendrites.